THE ROLE OF SOMATIC OBJECTS IN PAREMIOLOGICAL TEXTS (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the use of somatic objects in paremiological texts in English and Uzbek languages. Somatic objects are related to parts of the human body and are widely used in proverbs and idiomatic expressions. The article provides a comparative analysis of the cultural and psychological aspects of somatic phrases, as well as their linguistic peculiarities.
Keywords: Somatic objects, paremiology, phraseology, English language, Uzbek language, cultural characteristics, psychological analysis, linguistic comparison, metaphors, proverbs and sayings.